UPAYA INDONESIA MENGHAPUS BEA MASUK IKAN TUNA KE PASAR JEPANG - Adilah Yuliadista; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Indonesia is one of the countries with the largest tuna production in the world. This can be seen from Indonesia's exports which have increased almost every year with the aim of exporting to various countries. Japan is one of the main destinations for Indonesian tuna exports. The import duty on tuna to the Japanese market is subject to a tariff of 3.5 percent. Meanwhile, in the Indonesia-Japan Economic Partnership Agreement (IJEPA), it is stated that the import duty on tuna is abolished. Import duties on tuna in other ASEAN countries such as Thailand have been abolished. Therefore, this study aims to analyze Indonesia's efforts to eliminate the entry of tuna into the Japanese market. According to the liberal theory, trade relations can have an impact on increasing welfare. The theoretical point from this perspective is that conflict and cooperation will shape international affairs. The research method that the author uses is descriptive qualitative method and uses data collection techniques in the form of library research. The result of this research are by conducting economic diplomacy between Indonesia and Japan. Indonesia also carries out trade promotions through the Japan International Seafood and Technology Expo (JISTE) and Seafood Expo Global (SEG) exhibitions. Improving the quality of fisheries is also carried out by Indonesia with the aim that Indonesian fishery products, especially tuna, are increasingly well known by Japan. Keywords: economic diplomacy, IJEPA, import duty, tuna